2005
DOI: 10.1353/lib.2006.0017
|View full text |Cite
|
Sign up to set email alerts
|

Interface Design, Web Portals, and Children

Abstract: Children seek information in order to complete school projects on a wide variety of topics, as well as to support their various leisure activities. Such information can be found in print documents, but increasingly young people are turning to the Web to meet their information needs. In order to exploit this resource, however, children must be able to search or browse digital information through the intermediation of an interface. In particular, they must use Webbased portals that in most cases have been design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 35 publications
(33 reference statements)
2
15
0
3
Order By: Relevance
“…-Use sound and music to attract children's attention (Jakob Nielsen, 2010), use simple and relatively large fonts (Large & Beheshti, 2005), use images and interesting characters with special effects that should not be distracting and are also child-friendly (Jakob Nielsen, 2010), using narration in a friendly human voice with age-appropriate language (Borse, Robles, & Schwartz, 2006).…”
Section: Design Multimedia Designmentioning
confidence: 99%
“…-Use sound and music to attract children's attention (Jakob Nielsen, 2010), use simple and relatively large fonts (Large & Beheshti, 2005), use images and interesting characters with special effects that should not be distracting and are also child-friendly (Jakob Nielsen, 2010), using narration in a friendly human voice with age-appropriate language (Borse, Robles, & Schwartz, 2006).…”
Section: Design Multimedia Designmentioning
confidence: 99%
“…Les études sur le développement de sites Web pour la jeunesse Plusieurs études nous ont également fourni des pistes concernant le développement de sites Web jeunesse (Blowers et Bryan, 2004 ;Cooper, 2005 ;Druin, 2005a ;Druin, 2005b ;Large et Beheshti, 2005 ;Large, Nesset, Beheshti et Bowler, 2006 ;Large, Bowler, Beheshti et Nesset, 2007 …”
Section: Les Documents De Gestion Interneunclassified
“…In this section we describe one of the possible layouts that addresses the main concerns raised in studies observing children interacting with traditional search engine interfaces [8,9]. Figure 2 shows the interface layout that attempts to ease the cognitive load by minimising query-based interaction.…”
Section: Content Presentationmentioning
confidence: 99%
“…This leads to frequent revisiting of previous pages or 'looping', as well as spending less time reading a page [3]. Finally, it has been shown that children prefer a personalised interface that reflects their personality and interests [2,10,9], thus creating a more engaging experience.…”
Section: Introductionmentioning
confidence: 99%